The Influence of Liquidity, Firm Size, Investment Opportunity Set, and Profitability on Earnings Quality With Firm Value as a Moderating Variable - Siti Nahdiatusa Adah; Yudhi Herliansyah (Politeknik Siber Cerdika Internasional, 2025)
This study aims to examine and analyze the effect of liquidity, company size, investment opportunity set, and profitability on earnings quality with company value as a moderating variable. The research employs a quantitative approach utilizing panel data from LQ45 companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023 using 117 samples. The data analysis method involves panel data regression analysis and moderated regression analysis processed with Econometric Views 12 (E-Views 12). The results of this study show that liquidity has no significant effect on earnings quality, firm size has no significant effect on earnings quality, investment opportunity set has no significant effect on earnings quality, profitability has a significant effect on earnings quality. In addition, firm value as a moderating variable, moderates all independent variables as a predictor moderator on relationship between the influence of liquidity, firm size, investment opportunity set and profitability on earning quality. These findings provide impetus for LQ45 companies to consider earning's quality in order to increase the balance between earnings and cash flow and reveal earnings in their actual conditions. This research contributes novel insight that firm value can predict the relationship between liquidity, company size, investment opportunity set and profitability on the quality of a company's profits.